Development of A New Nurse Orientation Program in the Intensive Care Unit - Masitho Masitho; Rr Tutik Sri Haryati; Hanny Handiyani; Krisna Yetti; La Ode Abdul Rahman; Tuti Afriani (GLOBAL HEALTH SCIENCE GROUP, 2026)
The transition of newly graduated nurses into high-intensity environments such as Intensive Care Units (ICU) presents significant challenges, often resulting in psychological stress and a gap between theoretical knowledge and clinical practice. To bridge this gap, a structured and systematic orientation approach is essential. One proven method is preceptorship, in which senior nurses act as clinical mentors to support new nurses in their professional adaptation. This approach facilitates the development of professional identity, enhancement of clinical competence, and gradual internalization of a patient safety culture. Objective: To evaluate and strengthen the roles of head nurses and primary nurses in mentoring newly graduated nurses to optimize ICU orientation and enhance patient safety. A pilot project method was applied, beginning with problem identification, problem analysis, priority setting, development of a Plan of Action, implementation, and evaluation. The implementation of a preceptorship-based orientation program, supported by clear guidelines and checklists, improved the effectiveness of clinical mentoring by Primary Nurses in the ICU. Through a systematic change approach, the program successfully strengthened the role of preceptors, accelerated the adaptation of new nurses, and fostered a sustainable clinical learning culture. The preceptorship-based orientation program effectively facilitated the transition of newly graduated nurses into the ICU setting by enhancing clinical competence, confidence, and professional adaptation. Strengthening the role of preceptors and implementing structured guidelines fostered a supportive learning environment, reduced the theory–practice gap, and promoted a sustainable culture of patient safety and continuous professional development.